2008
DOI: 10.1101/gr.7229808
|View full text |Cite
|
Sign up to set email alerts
|

Multigenome analysis identifies a worldwide distributed epidemic Legionella pneumophila clone that emerged within a highly diverse species

Abstract: Genomics can provide the basis for understanding the evolution of emerging, lethal human pathogens such as Legionella pneumophila, the causative agent of Legionnaires’ disease. This bacterium replicates within amoebae and persists in the environment as a free-living microbe. Among the many Legionella species described, L. pneumophila is associated with 90% of human disease and within the 15 serogroups (Sg), L. pneumophila Sg1 causes over 84% of Legionnaires’ disease worldwide. Why L. pneumophila Sg1 is so pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
174
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 50 publications
15
174
2
3
Order By: Relevance
“…In addition, similar to the finding in L. pneumophila type IV substrates (5,22), several C. burnetii Dot/Icm substrates have more than one homolog in its genome (Table S6), which suggests that functional redundancy of T4SS substrates may also exist in C. burnetii. Furthermore, except for one protein (CBUA0014) encoded by a plasmid carried gene, only 18 substrates are fully conserved among C. burnetii isolates (Table S5), a phenomenon in contrast to L. pneumophila, in which T4SS substrates are highly conserved among different isolates of the same species (43). The majority of missing homologs were presented as pseudogenes in different isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar to the finding in L. pneumophila type IV substrates (5,22), several C. burnetii Dot/Icm substrates have more than one homolog in its genome (Table S6), which suggests that functional redundancy of T4SS substrates may also exist in C. burnetii. Furthermore, except for one protein (CBUA0014) encoded by a plasmid carried gene, only 18 substrates are fully conserved among C. burnetii isolates (Table S5), a phenomenon in contrast to L. pneumophila, in which T4SS substrates are highly conserved among different isolates of the same species (43). The majority of missing homologs were presented as pseudogenes in different isolates.…”
Section: Discussionmentioning
confidence: 99%
“…This region can be integrated in the chromosome but can also excise in a site-specific manner to exist as a low copy number plasmid that is undoubtedly transferable among strains (Doleans-Jordheim et al 2006). Indeed, it is present in five of the eight sequenced L. pneumophila strains, in L. longbeachae strain D-4968 (Kozak et al 2010), and according to hybridization results also partly in Legionella rubrilucens (Cazalet et al 2008). Interestingly, in the Legionella strains where the Lvh T4SS is not present, another Tra system, a Ptype T4SS that codes for short and rigid pili that allow surface mating for conjugation, is present in the same chromosomal position (Gomez-Valero et al 2011b).…”
Section: Phaeodactylum Tricornutummentioning
confidence: 99%
“…Likewise, L. longbeachae strain NSW150 possesses a plasmid of 72 kb, and also strain D-4968 seems to contain a plasmid (Kozak et al 2010). These replicons show a heterogeneous distribution among the different genomes, as the same plasmids or partially similar plasmids are present in different strains (Cazalet et al 2008). Likewise, a comparative analysis of these plasmids revealed that the 30.4 kb Tra region present in the plasmid of L. pneumophila strain Paris shows much higher identity with the Tra region located on the L. longbeachae plasmid, than with those of the other L. pneumophila strains sequenced (Gomez-Valero et al 2011b).…”
Section: Phaeodactylum Tricornutummentioning
confidence: 99%
See 2 more Smart Citations